Effects of symmetry breaking on learning a bimanual coordination pattern - Atchy-Dalama, P.; Zanone, P. G.; Peper, C.E.; Beek, P.J. (International Journal of Computer Science in Sport, 2002)
Viewed from a dynamical systems perspective, learning corresponds to a modification of the coordination dynamics in the direction of a to-be-learned pattern through the interplay of coopération-compétition between behavioral information (i.e., information specifying the to-be-learned pattern) and existing coordination tendencies. In the present experiment, we study the effect of a control parameter, namely the eigenfrequency difference between the coordinated limbs (Q ), on the acquisition of a bimanual coordination pattern. It has been shown that £2 ^ 0 results in symmetry breaking of the coordination dynamics by (1) a change in mean of <j> (i.e., the phase difference between the limbs) and (2) a change in the standard deviation of <j>. Thus, by manipulating Q before learning, it is possible to induce a shift of a pre-existing attractor toward a to-be-learned relative phase. As a result, the initial situation of competition becomes one of cooperation, prompting several important questions: Does learning in a symmetry breaking condition facilitate a stabilisation of the to-be-learned pattern? And, if so, does it help learning? And does learning in an asymmetric situation transfer to a symmetric situation ?